Shiitake mushroom bezoar: a rare cause of small bowel obstruction in Vietnam and lessons in diagnosis and management - Tri-Nhan Pham; Minh-Quang Tran; Phu-Cuong Pham; My-Tran Trinh; Quang-Duy Ngo; Kim-Long Le (Emergency Care Journal)
Small Bowel Obstruction (SBO) caused by shiitake mushroom bezoars is a rare clinical entity, with no prior cases documented in Vietnam despite the frequent consumption of these mushrooms in traditional dishes. We report the case of a 69-year-old male who presented with SBO symptoms after ingesting a whole shiitake mushroom without chewing due to significant molar tooth loss. Computed Tomography (CT) imaging revealed characteristic features of a bezoar, and exploratory laparoscopy confirmed an obstructing shiitake mushroom bezoar, which was removed via enterotomy. This case highlights the diagnostic challenges of radiolucent bezoars and the critical importance of dietary history and characteristic CT findings. Preoperative assessments could facilitate less invasive surgical strategies, reducing the risks associated with enterotomy, such as anastomotic leakage. Clinicians should remain aware of regional dietary practices to enhance diagnostic precision and optimize management strategies, especially in high-risk populations with compromised mastication.